LEGAL PROTECTION OF COPYRIGHT FOR COMPUTER PROGRAMS - Ramona Anca Denisa DUMITRAŞCU (Challenges of the Knowledge Society, 2016)
This article referes to the evolution of EEC’s reglementation of software judicial protection and its interpretation of the European Court of Justice. The conclusion is that the European judicial system is more precupied to develop a system of interoperability that will steer Europe towards the users interests as well as the economic interests of the market and nearly negligent towards the interests of the authors although it recognizes the moral rights and patrimonial rights which can be used in the limited framework which will permit a better understanding of the value of its creators through interoperability.